Analisis Pengaruh Perubahan Iklim Terhadap Kenaikan Harga Kebutuhan Pokok Di Pasar Sragi Menjelang Ramadan - Khasanah, Fadila Arifatu; Adinugraha, Hendri Hermawan (Studia Economica : Jurnal Ekonomi Islam, 2024)
This study aims to identify the prices of basic necessities that rise ahead of Ramadan, the effect of climate change on these price changes, and government actions to maintain price stability in the market. This descriptive research uses a qualitative approach. Primary and secondary data were used in this study. Data were obtained through observation, interviews, and documentation. This research found that the increase in the price of basic necessities in the market can be caused by various factors such as the imbalance between demand and supply, the availability of raw materials used, the phenomenon of climate change, the length of the distribution chain of goods, and stockpiling by middlemen. Some of the policies implemented by the government to reduce the price of basic commodities in the market include government subsidies, the implementation of fiscal policies, agricultural infrastructure development, and government supervision to maintain price stability.